Developing multicultural-based religious tourism in Jember - Ummi Subaniyah; Lolita Meilinda; Milawaty Milawaty; Uystka Hikmatul Kamiliyah NH (Journal of Enterprise and Development (JED), 2024)
Purpose — The purpose of this research is to analyze the potential development of multicultural-based religious tourism in Jember Regency, along with the arrangement of tour packages aimed at all societal groups as the final product.Method — This research is a descriptive-qualitative study with data collection techniques in the form of field observations, documentation, and literature studies.Result — The results show that Jember Regency, especially in the area around the city center, has the potential to develop multicultural-based religious tourism through the existence of religious tourism destinations, including Muslim, Christian, and Confucian places of worship with unique and cross-cultural (multicultural) architectural designs. The J-Versity tour package, which includes activities to visit these tourist destinations, is the product offered for the development of multicultural-based religious tourism in Jember Regency.Novelty — This research provides a new perspective on the development of religious tourism in Jember Regency through the multicultural concept presented. It also offers a prototype for organizing and managing religious tourism activities in the city through the J-Versity tour package. This is expected to have an impact since it targets all societal groups across cultures and beliefs.